THE EFFECT OF PARTIAL REPLACEMENT OF COMMERCIAL RATE WITH CONVENTIONAL RATING ON THE PHYSICAL QUALITY OF ISA BROWN CHICKEN EGGS - I D. G. A. A., Diningrat; Suasta, I M.; Astawa, I P. A. (Jurnal Peternakan Tropika; Vol 11 No 1 (2023): Vol. 11 No. 1 Tahun 2023; January - april, 2023)
The research which aims to determine the effect of partial replacement of commercial rations with conventional rations on the physical quality of Isa brown chicken eggs has been carried out in the cage owned by Mr. I Putu Ari Astawa located in Candikusuma Village, Melaya District, Jembrana Regency, for feed analysis carried out in the nutrition and nutrition laboratory. fodder, Faculty of Animal Science, Udayana University, Bali on October 10 - January 10, 2022. The study used a completely randomized design (CRD) consisting of 4 treatments and 4 replications. The treatments given were treatment P0 (chicken given commercial ration (PL 241), treatment P1 (chicken given conventional ration 1), treatment P2 (chicken given conventional ration 2), treatment P3 (chicken given conventional ration 3). The variables observed included egg weight, egg white percentage, egg yolk percentage, egg shell percentage, yolk color, and HU (Haugh Unit).The results showed that egg weight in P1 treatment was significantly higher (P<0.05) than P0, whereas with P2 it was not significantly different (P>0.05) and with P3 it was significantly lower (P<0.05) than P0. The percentage of egg whites did not show a significant difference (P>0.05) between treatments. The percentage of egg yolks in treatment P1, P2, and P3 was significantly lower (P<0.05) than P0. For the percentage of eggshells in treatment P0, it was significantly lower (P<0.05) than treatments P1, P2, and P3. Egg yolk color showed that P1 was significantly lower (P<0.05) than P 0, whereas with P2 it was not significantly different (P>0.05) and with P3 it was significantly higher (P<0.05) than P0. For Haugh units P1, P2, and P3 were significantly higher (P<0.05) than P0. Based on the results of this study, it can be concluded that partial replacement of commercial rations with conventional rations gave the same results on the percentage of egg whites but gave different results on egg weight, HU, and decreased the percentage of yolk and egg yolk color, and increased the percentage of egg shells compared to the diet. commercial. Keywords: rations, brown ice, physical quality eggs